The Effectiveness of the Case Method in Promoting Meaningful Learning and Enhancing Student Learning Outcomes - Munawwarah, Munawwarah; Ruslan, Zuhrah Adminira (Universitas Pendidikan Mandalika, 2025)
This study investigates the effectiveness of the case method in fostering meaningful learning and improving student learning outcomes. Using a quasi-experimental one-group pretest-posttest design, 20 chemistry education students participated in a series of learning activities centered around the case method. Data were collected through pretest and posttest essay assessments and analyzed using descriptive statistics and paired t-tests. Results showed a significant increase in the average student scores from 72.68 (pretest) to 85.21 (posttest), with a reduction in score variability, as evidenced by a t-statistic of -4.28 and a p-value of 0.00045. These findings indicate that the case method effectively enhances student understanding and promotes meaningful learning by engaging students in contextual problem-solving activities. This method aligns with constructivist learning theory and supports the development of essential skills such as critical thinking, collaboration, and the application of theoretical knowledge in practical contexts. Furthermore, its universal applicability across various disciplines highlights its potential to enhance educational practices. Future research should explore long-term impacts, optimize case selection, and examine integration with educational technologies.